Analisis Formulasi Pendaftaran Pemilih Pemilihan Umum Tahun 2019 Pada Komisi Pemilihan Umum Kota Medan - Fachrur Razi Juned; Marlon Sihombing; Abdul Kadir (PERSPEKTIF, 2021)
One of the requirements to be able to vote is to become a voter on the Final Voters List (DPT). In fact, this list is a classic problem that has never existed, including the DPT for the 2019 Concurrent Elections. Using qualitative methods, this thesis discusses why the DPT for the 2019 Election is still problematic, with the large number of voters in Medan City who vote using their KTP on polling day there are still voters who have not registered in the DPT who can reach more than 10% of the total number of DPT in Medan City and how to solve this problem. Even though Law no. 7/2017 concerning Election for voter registration using the registration registration method, the application of this method has not met the prerequisites. There are at least eleven prerequisites that must be met. The Election Law does not help who is responsible for implementing updating voter data in the post-election period. The current registration and updating formulation is more of an update on the system's ongoing periodic list. A timely voter registration formulation is implemented by the KPU by opening up spaces for cooperation between government agencies and institutions involved in updating population data. With a sustainable system, it is hoped that it can increase the degree of updating of data selectors.